Monocytic-Myeloid Derived Suppressor Cells Suppress T-Cell Responses in Recovered SARS CoV2-Infected Individuals - Beliakova-Bethell, Nadejda; Maruthai, Kathirvel; Xu, Ruijie; Salvador, Liliana C. M.; Garg, Ankita (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19) caused by SARS Coronavirus 2 (CoV2) is associated with massive immune activation and hyper inflammatory response. Acute and severe CoV2 infection is characterized by the expansion of myeloid derived suppressor cells (MDSC) because of cytokine storm, these MDSC suppress T cell functions. However, the presence of MDSC and its effect on CoV2 antigen specific T cell responses in individuals long after first detection of CoV2 and recovery from infection has not been studied. We and others have previously shown that CD11b+CD33+CD14+HLA-DR-/lo monocytic MDSC (M-MDSC) are present in individuals with clinical recovery from viral infection. In this study, we compared the frequency, functional and transcriptional signatures of M-MDSC isolated from individuals who were not infected with CoV2 (CoV2-) and individuals who were infected with CoV2, after 5-months following the first detection of the virus (CoV2+). Compared to CoV2- individuals, M-MDSC were present in CoV2+ individuals at higher frequency, the level of M-MDSC correlated with the quantity of IL-6 in the plasma. Compared to CoV2-, increased frequency of PD1+, CD57+ and CX3CR1+ T effector memory (TEM) cell subsets was also present in CoV2+ individuals, but this did not correlate with M-MDSC. Furthermore, depleting M-MDSC from peripheral blood mononuclear cells (PBMC) increased T cell cytokine production when cultured with the peptide pools of immune dominant spike glycoprotein (S), membrane (M) and nucleocapsid (N) antigens of CoV2. M-MDSC suppressed CoV2 S- antigen specific T cell in ROS, Arginase and TGFβ dependent manner. Our gene expression, RNA-seq and pathway analysis studies further confirm that M-MDSC isolated from CoV2+ individuals are enriched in pathways that regulate both innate and adaptive immune responses, but the genes regulating these functions (HLA-DQA1, HLA-DQB1, HLA-B, NLRP3, IL1β, CXCL2, CXCL1) remained downregulated in M-MDSC isolated from CoV2+ individuals. These results demonstrate that M-MDSC suppress recall responses to CoV2 antigens even after prolong recovery from infection. Our findings suggest M-MDSC as novel regulators of CoV2 specific T cell responses, and should be considered as target to augment responses to vaccine.